Restoration station roofs ‘s-Hertogenbosch (Bulletin KNOB, 1999)
The newly constructed railway station complex of 's-Hertogenbosch incorporates two 450-metre-long historical station roofs, which are currently under restoration. These were built at the end of the last century and constitute, as far as is known, the first steel structures to be used in a building in the Netherlands.During their lifetime, they suffered a lot of damage due to three types of problems. These problems were caused by a lack of knowledge on the loads they had to withstand, by different behaviour regarding temperature expansion than assumed in the 1890s and by technical details which made it impossible to maintain them locally.During the restoration process, these problems have had to be taken into account and solved in order to prolong the structure's lifetime by another century and to make maintenance possible. The aim has been to perform the restoration as discreetly as possible. Whereas the structure's restoration is not to catch anyone's eye particularly, an interested person should be able to see what has been done. For this reason, advantage is being taken of the fact that the object in question is an early steel structure. Corrections to the structure are being welded instead of riveted in order to demonstrate the fact that it is a steel structure and that the connection is not original.The colour scheme, which was modified a long time ago, has been investigated. This has not only made it possible to restore the spatial appearance of this historically important roof structure but also its original colours, which is very important from the perspective of architectural history. The result is astonishing. Both station roofs have been restored to their original splendour, ready for the next century.